Efecto de la aplicación de dos fungicidas para controlar sigatoka negra mycosphaerella fijiensis en una plantilla de banano musa spp - Valdiviezo Arias, Henry Braulio (2018)
The present work was carried out in an experimental area of the Unidad Académica the Ciencias Agropecuarias of the Universidad Técnica of Machala. Due to the problems that occur in the field especially in banana due to the fungus Mycosphaerella sp., Which is an ascomycete that arrives mainly attacking the foliar part of the plant, it is the most destructive and of greater economic value leading to obtain losses up to 50% in its performance. Without measures of control of this fungus you can have a 50% weight loss in a cluster and lose 100% of production due to deterioration in quality. Its name comes from the valley of Sigatoka in the fiji islands where it was spread to all countries of banana producers and where it was identified for the first time in 1912. After this it appeared in Central America in 1934, affecting the interest of the producers as merchants of the banana sector. The banana is one of the most exported, being in the fifth position of the countries of major banana exporters, according to the data extracted from TRADE MAP. The banana sector is one of the most stable in the country; from January to August of the year 2014, revenues of 1,664 million USD FOB were obtained, while for the same date of this year, revenues of 1,858 million USD FOB were obtained, a positive variation of 11.6%, with the United States being the main destination of a banana export. In the fieldwork carried out in the Unidad Académica the Ciencias Agropecuarias, the sowing of the banana stencils was executed at a height between 25 and 30 cm. For the cultural tasks, weed control was performed manually during the field stage. For this experimental work 4 treatments were performed with 5 repetitions, to determine the effect of a fungicide for the control of Black Sigatoka. Treatment 1 (Banana film 1L), Treatment 2 (banana film 1L + Bravo 1L), Treatment 3 (Bravo 1L) and Treatment 4 (control). The application of the different treatments was carried out on the right side of the leaf blade on leaf 1 and 2 of each plant applied with a CP3 pump. The preparation of the mixtures was carried out with 52.85 ml of product plus 947.15 of water, resulting in the final dose of 1,000 ml (1L), taking as variables the evaluation of the progress of the disease every 7, 14, 21, 28, 35, 42 days in sheets 1 and 2 of each treatment applied and determine the smallest area under the curve of progress of the disease (AUDPC). A Completely Alazar Block Design (DBCA) was used, to later perform the statistical tests. According to the results obtained in the evaluation of protective fungicide and adjuvant in sheets 1 and 2, the best treatments were T2 and T3 since they have a better control of the fungus. For the results of the area under the disease progression curve, for leaf 1 the T2 has a lower infection rate of (672.00) unlike the rest of the treatments and in leaf 2 the T3 has a lower infection rate of (677.60) unlike the rest of the treatments.